A look at reputation management in universities - Amado Mateus, Marelby; Juarez Acosta, Fernando (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Managers of higher education institutions (HEIs) have faced the challenges brought about by increased competition in the sector, and the difficulties in developing, communicating and positioning a differential in their academic proposals. This has implied a change in the strategic approach to marketing and university reputation management. However, there is still a lack of clarity about what reputation management implies in universities and what its dimensions are, so a structured literature review is proposed to answer these questions.